Social-Mediated Diffusion of Conspiracy Theories about COVID-19: A Study Integrating SMCC and TPB Models. Issue 7 (21st April 2022) - Li, Zitian; Qiu, Hongfeng; Zhou, Qianying
ABSTRACT: Two conspiracy theories that respectively attribute the origin of COVID-19 to a Chinese research institute and the US, were widely disseminated over China's social media sphere in early 2020. By integrating the social-mediated crisis communication model with the theory of planned behavior, this study investigates predictors of public reactions to these conspiracy claims. The results of a cross-sectional survey discovered that message strategies and forms as well as user types and emotions can variously predict their believing in and diffusing conspiracy theories. Rational appeal and internet efficacy both predict diffusing the theory that attributes its origin to the US but have no effect on diffusing its counterpart. Moreover, family discussion has no effect on diffusing both two theories. These findings suggest that public reactions to coronavirus-related conspiracy theories should be examined in the contexts of not only social media applications but also China's internet regulations, cultural values, and international relations.